SQL Server 2019 Administrator's Guide - Second Edition - Chmel, Marek (Packt Publishing, 2020)
Use Microsoft SQL Server 2019 to implement, administer, and secure a robust database solution that is disaster-proof and highly available Key Features Explore new features of SQL Server 2019 to set up, administer, and maintain your database solution successfully Develop a dynamic SQL Server environment and streamline big data pipelines Discover best practices for fixing performance issues, database access management, replication, and security Book Description SQL Server is one of the most popular relational database management systems developed by Microsoft. This second edition of the SQL Server Administrator's Guide will not only teach you how to administer an enterprise database, but also help you become proficient at managing and keeping the database available, secure, and stable. You'll start by learning how to set up your SQL Server and configure new and existing environments for optimal use. The book then takes you through designing aspects and delves into performance tuning by showing you how to use indexes effectively. You'll understand certain choices that need to be made about backups, implement security policy, and discover how to keep your environment healthy. Tools available for monitoring and managing a SQL Server database, including automating health reviews, performance checks, and much more, will also be discussed in detail. As you advance, the book covers essential topics such as migration, upgrading, and consolidation, along with the techniques that will help you when things go wrong. Once you've got to grips with integration with Azure and streamlining big data pipelines, you'll learn best practices from industry experts for maintaining a highly reliable database solution. Whether you are an administrator or are looking to get started with database administration, this SQL Server book will help you develop the skills you need to successfully create, design, and deploy database solutions. What you will learn Discover SQL Server 2019's new features and how to implement them Fix performance issues by optimizing queries and making use of indexes Design and use an optimal database management strategy Combine SQL Server 2019 with Azure and manage your solution using various automation techniques Implement efficient backup and recovery techniques in line with security policies Get to grips with migrating, upgrading, and consolidating with SQL Server Set up an AlwaysOn-enabled stable and fast SQL Server 2019 environment Understand ...